Hypoglycemic polysaccharides from Auricularia auricula and Auricularia polytricha inhibit oxidative stress, NF-κB signaling and proinflammatory cytokine production in streptozotocin-induced diabetic mice - Huan Xiang; Dongxiao Sun-Waterhouse; Chun Cui (Food Science and Human Wellness)
Auricularia auricula (AA) and Auricularia polytricha (AP) are popular edible fungi. This study successfully produced hypoglycemic polysaccharides from un-smashed or smashing and sieving (through a 10-mesh sieve) AA and AP (termed as AAP/AAP-10 and APP/APP-10) via scalable processes (water extraction, ethanolic precipitation and deproteinization). This is the first report to compare the effectiveness of AAP and APP in combating streptozotocin-induced oxidative stress and diabetes-related changes in mice (body weight, fasting blood glucose, serum insulin, proinflammatory mediator and cytokines, oxidative stress-related products, antioxidant enzymes). APP and AAP with different molecular weights and monosaccharide molar ratios could be therapeutic options for diabetes with a low dose (100 mg/kg/day) likely working better. At the same dose, APP generally performed more effective than AAP, and AAP-10/APP-10 seemed slightly more beneficial than AAP/APP. One mechanism underlying these antidiabetic functions might involve the NF-κB and associated signalling pathways. AP is cheaper than AA, thereby representing a favorable source of functional polysaccharides.